INTEGRASI UNSUR TRADISIONALISME KE DALAM UNSUR MODERNISME - Mandjarreki, Sakaruddin (Jurnal Berita Sosial, 2019)
In a sociological perspective, individuals are always in an ambivalent, duality, and inconsistent position. The pounding wave of globalization that triggered and spurred the spirit of modernization, has simultaneously positioned and even led individuals to the altar of dualism, namely deifying the side of modernity through a set of modern behavior but at the same time worshiping the essence of traditionalism by being reluctant to abandon its cultural and locality aspects. This behavior seems to confirm that between the past and the present time, of course, can be compromised, or more precisely it can be integrated in a format of life that is adaptive and flexible to both periods; traditional and modern.Tradition is the pinnacle of human intellectuality that was previously codified, constructed, implemented, and rooted through behavioral patterns to technology to support its collective life. The innovation that we know today in its more complex and sophisticated form is actually a reproduction of past traditions with a simple pattern.